(3QbGHI GdbVGA GdEOGQi Ydi bQGQGJ GdEOGQI GdYGeI (B: s (3OQGSI JMdjdjI ebGQfI Hjf GdfXGejf GdSYhOi h GdeUQi (B/ s - (3eMeO Hf Ydi Hf eMeO GdbMWGfi s; (3KQhJ HOhi s; (3LGeYI GdbGgQIs (3cdjI GdMbhbs ((3GdbGgQI (B: s (3cdjI GdMbhb(B-(3LGeYI GdbGgQI,s, 2010)
(3cGf GdSHH GdQFjSi dOQGSI gPG GdHMK gh EWdGY cd HGMK HCf GdeedcI GdYQHjI GdSYhOjI JeGQS GdQbGHI GdbVGFjI Ydi bQGQGJ GdEOGQI GdYGeI ef NdGd LgI bVGFjI CSfO EdjgG gPg GdegeI h gh eG jYQa HOjhGf GdeXGde GdPi CUHM dg GSJbdGdg GdJGe HfXQ LeY GdWYhf h GdJXdeGJ GdJi jbOegG GUMGH GdTGf VO HYV GdbQGQGJ GdJi JUOQgG GdEOGQI ai ehGLgI GdCaQGO (B: (3h Ydi gPG GdefhGd GbJVJ GdeUdMI HCf jchf gfGc JWhjQ dOjhGf GdeXGde ef NdGd efMg CaGb LOjOI deeGQSI gPg GdQbGHI HTcd cHjQ h eG MOK ef JZjQGJ LPQjI ai fXGe OjhGf GdeXGde NGUI HYO JTcjdg GdLOjO GdUGOQ YGe (B1428 (3jYWi OdjdG Ydi Cf OjhGf GdeXGde CUHM jeGQS gPg GdQbGHI HTcd cHjQ ef HSW fahPg Ydi JUQaGJ GdEOGQI h HSW GdYOd h aQV QbGHJg Ydi bhGYO h eHGOF GdfXGe GdEOGQi GdeYehd Hg MGdjGs
The main reason for this research study is to inform every. researcher that the Kingdom of Saudi Arabia exercises judicial control over public administration decisions through the judicial body entrusted with this task. This is known as the Board of Grievances which has become a fully independent to consider all appeals and grievances provided by stakeholders against some decisions issued by the public administration in the face of individuals. In this vein, interest requires that the Board of Grievances must be developed by opening new horizons for the exercise of such judicial control significantly. The historical development which occurred to keep developments of service in the field of judicial control over public administration decisions means that the Board of Grievances has exercised this judicial control correctly
(3GWQhMI (B((3eGLSJjQ(B) - (3LGeYI GdbGgQI (B- (3cdjI GdMbhb (B- (3bSe GdbGfhf GdYGe, (B2010s
(3jTJed Ydj EQLGYGJ HdjhLQGajI(B: (3UaMI (B150-173s
(3GdfU HGdYQHjI hGdedNU HGddZI GdEfLdjRjI hGdYQHjI(B.s
Keywords: (3GdbGfhf GdYGes; (3GdfXGe GdSYhOi h GdeUQis; (3QbGHI GdbVGA GdEOGQis; (3bQGQGJ GdEOGQI GdYGeIs; (3OjhGf GdeXGdes; (3JbSje GdbQGQGJ GdGOGQjIs; (3eYGjjQ JejR GdbQGQ GdGOGQi hGQcGfg aj GdeedcIs; (3WQb JMQjc GdOYhi GeGe OjhGf GdeXGdes; (3JTcjd hGNJUGU OjhGf GdeXGdes; (3OYhi GdZGA GdbQGQGJ GdGOGQjI ai GdfXGe GdSYhOis; (3QSGFd LGeYjIs -- (3LGeYI GdbGgQIs -- (3GdbGfhf GdYGes